A Study on the Use of Mixed Language in Teaching English at Hospitality Management Class - Supartini, Ni Luh; Agustini, Ni Putu Oka (Journal of Business on Hospitality and Tourism, 2021)
Learning English as a foreign language required some strategies to achieve the goal of communication. In teaching and learning process, the teacher and students frequently use their first language to explain the difficult word in English. This study aimed to investigate the language used by the teacher as communication strategies in teaching English as a foreign language and students’ responses toward the use of each type of language instruction in teaching English at Hospitality class. To investigate the study there were 2 teachers and 2 classes of hospitality management class as the subject. The data were collected through observation of teaching and learning process and interview session. The study was designed as descriptive qualitative research and the data were analyzed descriptively. The finding showed that the teacher used the target language frequently, however the used of mixed language to explain some difficult words also found in teaching and learning process.